2022
DOI: 10.4314/ahs.v22i2.14
|View full text |Cite
|
Sign up to set email alerts
|

Acute flaccid paralysis incidence rate and epidemiology in children in Lebanon: a rise in numbers in the post-vaccination and refugee crisis era

Abstract: Background: Acute flaccid paralysis (AFP) is a clinical syndrome characterized by the acute onset of weakness and paralysis with reduced muscle tone. This study explored the incidence and different aspects of AFP in Lebanese children between 2009 and 2019. Methods: AFP data were collected from the Lebanese Ministry of Public Health. Incidence rate according to year, age groups, clinical data, follow-up, diagnosis, and vaccination status was analyzed in the 11-years period. Results: AFP incidence ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…A retrospective study conducted in Lebanon from 2009–2019 on 631 pediatric patients with acute flaccid paralysis showed that GBS accounted for 32.1% of the cases [ 59 ]. In order to rule out metabolic or electrolyte dysfunctions, as well as infections that can cause acute flaccid paralysis [ 60 ], we performed laboratory testing guided by the differential diagnosis with complete blood counts and studies of glycemia, electrolytes, liver and renal functions.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study conducted in Lebanon from 2009–2019 on 631 pediatric patients with acute flaccid paralysis showed that GBS accounted for 32.1% of the cases [ 59 ]. In order to rule out metabolic or electrolyte dysfunctions, as well as infections that can cause acute flaccid paralysis [ 60 ], we performed laboratory testing guided by the differential diagnosis with complete blood counts and studies of glycemia, electrolytes, liver and renal functions.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, el Síndrome de Guillain-Barré (SGB) prevalece como el diagnóstico más común, seguido por la mielitis transversa y las polineuropatías, entre otras condiciones. ; la importancia de la vigilancia de comportamientos inusuales del SBG es esencial para el control y la erradicación global de la poliomielitis (14).…”
Section: Situación Epidemiológica En Américaunclassified
“…Etiological factors behind AFP are multiple, including both infections and non-infectious causes 6 . Infections mainly occur due to viruses and bacteria, whereas non-infectious causes may include neurological lesions, trauma, toxic exposure, cancer, and other factors 7 . Evidence suggests that more than 50% of AFP is caused by Guillian-Barree Syndrome (GBS), an autoimmune disease with multiple etiology 8 .…”
Section: Introductionmentioning
confidence: 99%